2023
DOI: 10.1007/s00705-023-05773-y
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocytes in COVID-19: a tale of harmony and discordance

Abstract: B lymphocytes play a vital role in the human defense against viral infections by producing specific antibodies. They are also critical for the prevention of infectious diseases by vaccination, and their activation influences the efficacy of the vaccination. Since the beginning of coronavirus disease 2019 (COVID-19), which became the main concern of the world health system, many efforts have been made to treat and prevent the disease. However, for the development of successful therapeutics and vaccines, it is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…B lymphocytes play a pivotal role in the human defense against viral infections by generating targeted antibodies. Additionally, they are crucial for preventing infectious diseases through vaccination [27]. Therefore, it is no coincidence that a positive correlation between B lymphocytes (CD19+) and anti-SARS-CoV-2 antibodies IgG titers in the maintenance dialysis patients group was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…B lymphocytes play a pivotal role in the human defense against viral infections by generating targeted antibodies. Additionally, they are crucial for preventing infectious diseases through vaccination [27]. Therefore, it is no coincidence that a positive correlation between B lymphocytes (CD19+) and anti-SARS-CoV-2 antibodies IgG titers in the maintenance dialysis patients group was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, we found that the percentage of CD19 + B cells was lowest in patients on GCs and csDMARDs. As B cells play a fundamental role in the prevention of COVID-19 ( 35 ), whether the low proportion of B cells is associated with a high rate of infection in these patients requires further validation.…”
Section: Discussionmentioning
confidence: 99%
“…The humoral immune response by B-lymphocytes is part of the adaptive immune mechanisms, controlling viral infections through the neutralizing antibodies and antibody-dependent cellular toxicity ( 212 , 213 ). The elimination of viral infection and the apoptosis of virally infected cells is also provided by B lymphocytes through effector molecules, exhibiting antibody-independent functions ( 214 ).…”
Section: Avoidance Resistance and Tolerance To Virusesmentioning
confidence: 99%
“…The elimination of viral infection and the apoptosis of virally infected cells is also provided by B lymphocytes through effector molecules, exhibiting antibody-independent functions ( 214 ). However, lack of B cells has been associated with a mild form of COVID-19 suggesting that inflammatory cytokines, especially IL-6, may have a central role in the disease severity ( 213 ). In fact, patients with agammaglobulinemia (caused by a lack of B lymphocytes), show mild symptoms, short duration, and no need of treatment by IL-6 inhibitors, while patients exhibiting variable immune deficiencies with dysfunctional B lymphocytes, (also showing significant low levels of immunoglobulins in the serum), show severe outcomes and require mechanical ventilation, antiretroviral agents and IL-6-blocking agents ( 215 ).…”
Section: Avoidance Resistance and Tolerance To Virusesmentioning
confidence: 99%